Exosomal hsa-miR199a-3p Promotes Proliferation and Migration in Neuroblastoma - Ma, Jing; Xu, Min; Yin, Minzhi; Hong, Jie; Chen, Haoyan; Gao, Yijin; Xie, Chenjie; Shen, Nan; Gu, Song; Mo, Xi (Frontiers in Oncology, 2019)
Neuroblastoma (NB) is the most common pediatric extra-cranial solid tumor with heterogeneous characteristics, and the prognosis of patients with high-risk NB is usually poor. Discovery of novel biomarkers for early detection and investigation of the underlying mechanisms governing invasion and metastasis of NB are urgently needed. Recently, exosomal microRNAs (miRNAs) have been shown to play vital regulatory or communication roles in the process of various types of cancers. However, the roles and mechanisms of exosomal miRNAs in NB remain unknown. Thus, the present study aims to investigate the detailed functions of tumor-derived exosomal miRNAs in progression and metastasis migration of NB in vivo and in vitro. By examining different exosomal miRNA expression profiles in the plasma of NB patients, we identified that the expression of hsa-miR199a-3p from exosomes was significantly upregulated, which was correlated with the severity of NB patients. Furthermore, we confirmed that exosomal hsa-miR199a-3p could facilitate proliferation and migration of NB via regulating NEDD4 expression. In summary, our data, for the first time, revealed that exosomal hsa-miR199a-3p could promote tumor proliferation and migration via decreasing NEDD4 expression in NB, suggesting that exosomal hsa-miR199a-3p may be applicated as an early a fast, easy and non-invasive detection biomarker and contribute to the development of novel therapeutic strategies for NB in the future.